SLOPE STABILITY ANALYSIS OF HIGHWALL OF 10BC3 PIT PT. ARUTMIN INDONESIA JOBSITE KINTAP, SOUTH KALIMANTAN - Kurnia Viona, Steffani
PT. Arutmin Indonesia is a coal mining company that carries out their operation in South Kalimantan area using the open pit method. Kintap site is developing pit 10 by making a boxcut due to the discovery of an economic seam under the target seam of previous pit. As consequence, a highwall of pit 10BC3 is developed under the IPDC dump and pit 10’s sump. Therefore, a recommendation related to the geometry of pit 10BC3 highwall that comply with government safety standards is required. Slope stability analysis is conducted using Slide 6.0 software, the probability of failure and safety factor of the slope are calculated using the Monte-Carlo and Bishop Simplified methods. The distribution of the data used are determined by applying goodness of fit test such as the Kolmogorov-Smirnov and Akaike Information Criterion methods. The results of analysis show that the existing slope is considered safe because FoS deterministic = 1.610, FoS mean = 1.761 and PoF = 2.2%, however, the given slope geometry recommendation is considered unsafe because the PoF = 7.7% which exceeds the maximum limit of 5 %. In order to make a stable and safe highwall during coal getting operation, some safety precautions must be carried out which are draining the highwall sump and creating a slope-counterweight after coal getting.